Perkembangan Terkini Penyakit Influenza dan Peran Favipiravir dalam Tata Laksana Penyakit - Anna Rozaliyani; Asiyah Taqiyya Fakhrur Razi; Ammar Abdurrahman Hasyim; Findra Setianingrum; Rulliana Agustin; Erlang Samudro; Alvin Kosasih (MEDICINUS, 2025)
Influenza virus infection remains a major global health challenge, particularly for vulnerable groups with compromised immune systems. Influenza is primarily caused by infection of influenza A and B viruses, with a varying clinical spectrum, ranging from asymptomatic cases to life-threatening conditions. Influenza viruses tend to undergo rapid genetic mutations, limiting the long-term effectiveness of vaccine-induced immune responses. Diagnosing influenza remains challenging due to the nonspecific signs and symptoms of the disease. The gold standard for influenza diagnosis is reverse transcription polymerase chain reaction (RT-PCR) test. Antiviral drugs are an essential prophylactic and therapeutic strategy to reduce influenza-related morbidity and mortality, especially in high-risk populations. Favipiravir has the potential to be a promising therapy against influenza, SARS-CoV-2, and other RNA virus infections. Prevention and control of influenza virus infections, including vaccination, are management strategies that must be optimized.